2000
DOI: 10.1007/pl00008681
|View full text |Cite
|
Sign up to set email alerts
|

Foxy: an active family of short interspersed nuclear elements from Fusarium oxysporum

Abstract: A novel family of short interspersed nuclear elements (SINEs) has been identi®ed in Fusarium oxysporum. This family has been called Foxy. The feature that makes Foxy unique among SINEs is the presence of 5¢ terminal tetranucleotide repeats. Both the number and the sequence of these repeats vary between individual members of the family. The genome of F. oxysporum f. sp. lycopersici contains at least 160 copies of Foxy. In a mutant obtained upon gamma irradiation of a wild-type isolate, 13 new Foxy insertions we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
33
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 37 publications
2
33
0
Order By: Relevance
“…Among the retrotransposons of the SINE type already isolated (Table 1) the foxy element showed activity after gamma radiation treatment and subsequent new insertions (Mes et al, 2000).…”
Section: Transposable Element Structure and Distribution In Fungimentioning
confidence: 98%
See 2 more Smart Citations
“…Among the retrotransposons of the SINE type already isolated (Table 1) the foxy element showed activity after gamma radiation treatment and subsequent new insertions (Mes et al, 2000).…”
Section: Transposable Element Structure and Distribution In Fungimentioning
confidence: 98%
“…immersus N. crassa Nectria haematococa Goyon et al, 1996Cambareri et al, 1998Shiflett et al, 2002 Kim et al, 1995Mes et al, 2000Kachroo et al, 1995Wei et al, 1996Rasmussen et al, 1993 pathogenic mutant were isolated and it was shown that by insertion of the impala element a pathogenicity gene could be cloned and sequenced (ORP1) which is essential for the penetration of M. grisea into the host leaf tissue. This gene did not present homology with known genes, showing the potential of transposable elements for cloning of pathogenicity genes.…”
Section: Transposable Element Structure and Distribution In Fungimentioning
confidence: 99%
See 1 more Smart Citation
“…Ten transposons have been reported in Fusarium species (for review, see Wostemeyer and Kreibichl 2002), and one of them, Foxy (Mes et al 2000), was used in this experiment. Foxy is a short interspersed element (SINE) found in F. oxysporum f. sp.…”
mentioning
confidence: 99%
“…Foxy in F. oxysporum strain F9 was cloned by polymerase chain reaction (PCR) under conventional conditions using total cell DNA and primers 5Ј-C T G G G T G G C T G TA AC G A AG C C -3 Ј a n d 5 Ј-GGAATTTTGAGAGAGTTCGCCT-3Ј. These primers were synthesized based on the terminal sequence of Foxy in the strain Fo1007 (Mes et al 2000). The cloned fragment consisted of 546 nucleotides and it contained two putative RNA polymerase binding sites (data not shown).…”
mentioning
confidence: 99%